The Role of Financial Literacy, Access of Finance, Financial Risk Attitude on Financial Performance. Study on SMEs Jogjakarta - R. Heru - Kristanto HC (University of Merdeka Malang, 2022)
Micro, small and medium enterprises (SMEs) contribute significantly to economic development. Financial literacy, access to finance, and attitudes toward financial risk play a key role in improving the performance of SME participants. The primary aim of this study is to examine the impact of financial literacy on access to finance, attitudes to financial risk, and financial performance. The impact of financial literacy on home improvement financial performance examines the mediators of access to finance and attitudes to financial risk. Statistical analysis model used mediated regression. The research sample is the Actors' SMEs in Yogyakarta. The sampling technique was purposive sampling. Respondents were SMEs as many as 276 entrepreneurs. The mediation regression analysis tool uses PLS. The results of the research show: 1) Financial literacy has a positive effect on financial performance. 2) Financial literacy has a positive impact on access to finance. 3) Access to finance mediates the impact of financial literacy on financial performance. 4) Financial literacy has a positive impact on attitudes toward financial risk. 5) Attitudes to financial risk mediate the impact of financial literacy on financial performance. Survey results recommend the importance of improving financial literacy, easy access to finance, and attitudes toward financial risks. You need the ability to analyze small business risks to improve your company's financial performance and sustainability. Providing financial education to entrepreneurs requires the will of state agencies, the entrepreneurs themselves, and educational institutions.